Formation of Competencies in Higher Education by Bachelors and Masters - OBEDKOVA, Larisa Pavlovna; EFREMOV, Andrey Aleksandrovich; SEKERIN, Vladimir Dmitriyevich; GOROKHOVA, Anna Evgenievna; SLEPOV, Vladimir Alexander (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT In recent years, in higher education, there has been a transition to a competency-based model of education, the purpose of which is the formation of a socially and professionally competent person. The integration of higher education in research is the main idea of the competency-based approach. Such a model for the formation of research competencies of a bachelor/master should be the basis for creating an effective system for the development of professional competence through the development of research skills, the realization of creative abilities, improving the quality of education.RESUMEN En los últimos años, en la educación superior, ha habido una transición hacia un modelo de educación basado en competencias, cuyo propósito es la formación de una persona social y profesionalmente competente. La integración de la educación superior en la investigación es la idea principal del enfoque basado en competencias. Tal modelo para la formación de competencias de investigación en una licenciatura / maestría, debe ser la base para crear un sistema efectivo y desarrollar competencias profesionales y habilidades de investigación.